Household washing solutions to improve safety of fresh produce. - Shahi, Naresh. (Tufts University. Tisch Library., 2016)
This poster covers data from an intervention staged by NTAG surrounding washing solutions for food. Presented at the 2014 Scientific Symposium in Kathmandu Nepal.; Nutrition School: NIL Symposium Presentations, 2014.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy